Aplikasi Panic Buton Untuk Keamanan Warga Berbasis Android - Torkis Nasution; Wilda Susanti; Yandri Armi; Rangga Rahmadian Yuliendi (Universitas Hamzanwadi, 2022)
Citizens highly expect environmental security, but criminality is inevitable. The level of crime in the community brings unrest and discomfort, so a security system is needed that is connected with the officers concerned. This study aims to build a security system application connected to environmental security officers. This system can help the public provide reports quickly through the panic button application embedded in Android. System development using the spiral model method. A spiral model is an evolutionary software process model assembling the interactive nature of the prototype using control and systematic aspects of a linear sequential model. Meanwhile, the system design stage uses the Unified Modeling Language (UML). The application is in Android Studio for the design stage, a unique Integrated Development Environment (IDE) that runs on the Android platform. The panic button application is a security system designed to assist the public in providing reports and make it easier for security officers to follow up on the messages given. Accelerate the follow-up process of crimes because it is based on Android.